Residual stress determination in a C-C composite consisting of a carbonized elastomer matrix filled with graphite, carbon black and short carbon fibers - Statnik, Eugene S.; Ignatyev, Semen D.; Salimon, Alexey I.; Stepashkin, Andrey A.; Korsunsky, Alexander M. (Frontiers in Physics, 2024)
In this study, composites obtained through low-temperature carbonization of elastomeric matrix highly filled with graphite, carbon black and short carbon fibers were studied for the purpose of determining residual stresses at different scales using a combination of several complementary methods. The state-of-the-art techniques included X-ray stress analysis using the sin 2 𝜓 method, the micro-ring-core technique via Focused Ion Beam milling and Digital Image Correlation (FIB-DIC), the contour method, the strain gauge method, and hole drilling technique with digital laser speckle pattern interferometry (DLSPI). It was found that the contour method could not be used for residual stress evaluation due to the low electrical conductivity of composite.Moreover, the DLSPI hole drilling method did not reveal any fringes indicating that the residual stress level was insignificant and did not exceed a few MPa. The strain gauge method also revealed a narrow residual stress distribution with an average value of approximately zero. In contrast, the X-ray sin 2 𝜓 method as well as FIB-DIC technique both returned values of about 150...250 MPa.A hierarchical model of the composite is proposed along with the Davidenkov Type I-II-III stress classification that provides an explanation of these observations.